PENGARUH PENGGUNAAN MODEL PEMBELAJARAN TIPE COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TERHADAP HASIL BELAJAR EKONOMI PESERTA DIDIK KELAS X SEMESTER GENAP SMA NEGERI 1 METRO - Kurniawati Riski; Ningrum Ningrum (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
The CIRC learning model is a collaborative based learning model through a reading and writing approach and oral and written language arts. In the learning process, the model forms a heterogeneous group that is responsible for the group's tasks so that more meaningful understanding and learning are formed. The problem in the research conducted by researchers is